Venous stasis retinopathy complicating a case of cavernous-carotid fistula with an initial normal computed tomography angiogram of the brain - Cheng, TC; Jemaima Che Hamzah,; Safinaz Mohd Khialdin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Carotid-cavernous fistula (CCF) can be spontaneous or due to trauma. Due to its complication to the eye, diagnosis and intervention should not be delayed. We report a case of an elderly female who presented with left eye redness with gradual onset of protrusion over the same eye. She was suspected to have CCF with the clinical presentation. Nevertheless, she had a normal computed tomography diagnosis of CCF was confirmed. However, due to delay in diagnosis and treatment, the patient developed venous stasis retinopathy and neovascular glaucoma. Her vision remained poor despite aggressive systemic and ocular treatments. This case report is to emphasise the importance of clinical suspicion of a disease despite a normal imaging. This is to prevent irreversible blindness and other systemic complications. angiogram of the brain. Later, she was scheduled for cerebral angiography and the